IMPLEMENTASI SENSOR PHOTOCELL DAN PENANGKAL PETIR PADA PRODUK UMBRELLA ENERGY - Arief Dwi Ramadhan; Rahmat Hidayat; Lela Nurpulaela (LPPM Poltek ST Paul, 2020)
In the use of multifunctional umbrellas using a Suya Panel with Photocell Sensor, or known by the term Umbrella Energy is one of the renewable energy by utilizing sunlight that produces an electrical energy, where solar panels and batteries can convert an electrical energy. The power of the battery can store energy by changing the DC or AC current, a multifunctional umbrella is given a solar panel to absorb solar energy as a center for mobile chargers handphone as well as a place to relax. This multifunctional umbrella has been designed and modified on the umbrella roof to absorb sunlight. In this study, 3 Solar Panels with a capacity of 30 WP are used, in which the energy produced by the Solar Panel is then stored in batteries (batteries) with a capacity of 12 volts 20 Ah. The inverter used in this study has a capacity of 300 watts as a DC 12 voltage converter volts to 220 volt AC, which will then be used as a source of electrical energy.